Nutritional considerations for improved lean value - Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1989)
The swine industry is in a transitional period as it gears up to produce the lean meat required by the consumer. In fact, pork processors arc increasing the production of lean products (boneless loins, 95% fat-free hams) because consumers are willing to pay premiums for low-fat products. New methods of measuring the amount of lean pork (fat-a-meter, etc.) are being developed rapidly, in order to allow the packer to offer price differentials for lean compared to fat pigs. Pork producers, in my opinion, will adjust production systems to meet consumer demands for lean pork when monetary differentials are offered by the packer for high lean-value carcasses.; Swine Day, Manhattan, KS, November 16, 1989
Keywords: Swine day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-163-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 581; Swine; Split-sex feeding; Genotype; Lean growth; Biotechnology